Multicentre surveillance study on feasibility, safety and efficacy of antifungal combination therapy for proven or probable invasive fungal diseases in haematological patients: the SEIFEM real‐life combo study. Issue 6 (23rd December 2013) - Candoni, A.; Caira, M.; Cesaro, S.; Busca, A.; Giacchino, M.; Fanci, R.; Delia, M.; Nosari, A.; Bonini, A.; Cattaneo, C.; Melillo, L.; Caramatti, C.; et al.
Summary This multicentre observational study evaluated the feasibility, efficacy and toxicity of antifungal combination therapy (combo) as treatment of proven or probable invasive fungal diseases (IFDs) in patients with haematological malignancies. Between January 2005 and January 2010, 84 cases of IFDs (39 proven and 45 probable) treated with combo were collected in 20 Hematological Italian Centres, in patients who underwent chemotherapy or allogeneic haematopoietic stem cell transplantation for haematological diseases. Median age of patients was 34 years (range 1–73) and 37% had less than 18 years. Acute leukaemia was the most common underlying haematological disease (68/84; 81%). The phase of treatment was as follows: first induction in 21/84 (25%), consolidation phase in 18/84 (21%) and reinduction/salvage in 45/84 (54%). The main site of infection was lung with or without other sites. The principal fungal pathogens were as follows: Aspergillus sp. 68 cases (81%), Candida sp. six cases (8%), Zygomycetes four cases (5%) and Fusarium sp. four cases (5%). The most used combo was caspofungin+voriconazole 35/84 (42%), caspofungin + liposomal amphotericin B (L‐AmB) 20/84 (24%) and L‐AmB+voriconazole 15/84 (18%). The median duration of combo was 19 days (range 3–180). The overall response rate (ORR) was 73% (61/84 responders) without significant differences between the combo regimens. The most important factor that significantly influenced the response was granulocyte (PMN) recovery (P 0.009). Only one patient discontinued therapy (voriconazole‐related neurotoxicity) and 22% experienced mild and reversible adverse events (hypokalaemia, ALT/AST increase and creatinine increase). The IFDs‐attributable mortality was 17%. This study indicates that combo was both well tolerated and effective in haematological patients. The most used combo regimens were caspofungin + voriconazole (ORR 80%) and caspofungin + L‐AmB (ORR 70%). The ORR was 73% and the mortality IFD related was 17%. PMN recovery during combo predicts a favourable outcome. Clinical Trials Registration: NCT00906633.